Spontaneous adenocarcinoma of the gas gland in Nothobranchius fishes - Dyková, Iva; Blažek, Radim; Součková, Kamila; Reichard, Martin; Slabý, Ondřej (Diseases of aquatic organisms, 2020)
Nothobranchius fishes (Cyprinodontiformes), known for their genetically encoded extremely compressed lifespan, are considered an excellent vertebrate model for the research of aging. Unlike the rapid accumulation of data concerning their biology, ecology and genome, knowledge of their age-related diseases, including tumours, is still very limited. This Note reports spontaneous neoplastic lesions in the swim bladder gas glands of Nothobranchius furzeri, N. kadleci and N. orthonotus. Based on light and transmission electron microscopy, the neoplastic proliferation of gas gland cells was classified as adenocarcinoma. There was a concurrent proliferation of haemopoietic cells in the kidney interstitium in all individuals diagnosed with this type of primary neoplasia.
Keywords: Aging; Animals; dlouhověkost; zvířata; Adenocarcinoma; Longevity; Spontaneous neoplasia; adenokarcinom; stárnutí; Nothobranchius fishes; Gas gland adenocarcinoma; Cyprinodontiformes